The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24171/j.phrp.2017.8.5.05
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Itraconazole against Echovirus 30 InfectionIn Vitro

Abstract: ObjectivesEchovirus 30 is a major cause of meningitis in children and adults. The aim of this study was to investigate whether the antifungal drug itraconazole could exhibit antiviral activity against echovirus 30.MethodsThe cytopathic effect and viral RNA levels were assessed in RD cells as indicators of viral replication. The effects of itraconazole were compared to those of two known antiviral drugs, rupintrivir and pleconaril. The time course and time-of-addition assays were used to approximate the time at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Conversely, in a hepatocyte cell line (Huh-7), itraconazole shows significant toxicity and no selective inhibition of EBOV replication. In addition to its antifungal properties, recent research has identified itraconazole as a potential cancer treatment and as an inhibitor of several viruses, including influenza virus, enteroviruses and coronaviruses [46][47][48][49][50]. The mechanisms for these newly discovered functions appear unrelated to its antifungal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a hepatocyte cell line (Huh-7), itraconazole shows significant toxicity and no selective inhibition of EBOV replication. In addition to its antifungal properties, recent research has identified itraconazole as a potential cancer treatment and as an inhibitor of several viruses, including influenza virus, enteroviruses and coronaviruses [46][47][48][49][50]. The mechanisms for these newly discovered functions appear unrelated to its antifungal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Because workforce perceive expertise, skills, knowledge and new ideas as the sources of competitive advantages, they sometimes reluctant to share with others [2]. This implies that individuals will be reluctant to share if the exchange does not benefit them [4].…”
Section: Visibility Improvementmentioning
confidence: 99%
“…In fact, previous studies in various field found that many workforce consider knowledge transfer practice as threats to his/her wellbeing. By transferring knowledge, others may have the opportunity to outpace the job promotions [1,2]. In reciprocal perspective, knowledge transfer or knowledge sharing may occur to two or more people when knowledge sharing intention is visible to both parties [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal drugs Amphotericin B Impairing the attachment and internalization of the virus by host cells. In vitro Enterovirus 71 [ 96 ] Posaconazole Affecting intracellular cholesterol distribution by targeting oxysterol-binding protein In vitro Dengue virus [ 39 ] Itraconazole Suppressing viral RNA replication or polyprotein processing In vitro Enterovirus 71 [ 93 ] Affecting intracellular cholesterol distribution by targeting oxysterol-binding protein In vitro Dengue virus [ 39 ] Caspofungin Acting on viral main protease (Mpro) In silico SARS-CoV and SARS-CoV-2 [ 63 ] Acting on viral nonstructural protein 12 In vitro SARS-CoV-2 [ 64 ] 3. Antiprotozoal agents Quinine Indirectly by inducing host cell defense mechanisms In vitro HSV-1 [ 16 ] Interfering with terminal glycosylation in Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%